Penerapan Acceptance And Commitment Therapy (ACT) Untuk Menurukan Derajat Stres Pengasuhan - Rahayu Oktama Wardani; Hendriati Agustani; Langgersari Elsari Novianti (Universitas Islam Indonesia, 2017)
Having child who has intellectual disability brings out parenting stress toward mother. This research was carried out to obtain an intervention program design by using Acceptance and Commitment Therapy principles to decrease the level of parenting stress mother who has a mild intellectual disability child among 6-12 years old. After designing, the module of intervention was tried out by quasi-experimental method with pretest-posttest one-group design, involving two participants who are the mother of a Mild Intellectual Disability child that used a purposive sampling technique. The data were obtained through interviews, observations, and questionnaires. This research shows that the module can be used to decrease the level of parenting stress.Keywords: Acceptance and Commitment Therapy (ACT), parenting stress, psychological flexibility, the mother who has a mild intellectual disability child.